INDIUM(III) CHLORIDE COMPLEXING AND SOLVATION IN HYDROTHERMAL SOLUTIONS TO 350°C: AN EXAFS STUDY - Seward T.M.; Henderson C.M.B.; Charnock J.M. (My University, 2000)
X-ray absorption fine structure (EXAFS) measurements on indium(III) nitrate and perchlorate solutions from 25°C to 250°C at the saturated vapour pressure indicate that the In3+–oxygen (water) distance remains constant at 2.14 (±0.01) Å with an octahedral configuration. In 1.00 m HClO4 solutions, the formation of the In3+-perchlorate ion pair, In(ClO4)(H2O)52+, was detected in which the In3+–chlorine (perchlorate) distance varied from 3.14 to 3.12 Å with increasing temperature to 250°C. In 0.10 m HCl solutions at 25°C, octahedrally coordinated InCln(H2O)6−n3−n (0≤n≤4) complexes are present in which the In3+–chloride and –oxygen (water) distances are 2.40 and 2.13 Å, respectively. With increasing temperature to 300°C, the complex geometry becomes predominantly tetrahedral with the formation of InCl4− having an In3+–chloride distance of ~2.37 Å. In concentrated 1.00 m InCl3 (no added HCl) solutions, indium–indium interactions (4.10 Å) were also noted together with enhanced In3+–oxygen distance contraction (i.e., 2.18 to 2.10 Å) in the temperature range from 25°C to 300°C due to the loss of two water molecules from the first shell environment, leaving a more tightly bound OH− ligand.The data demonstrate the lack of contraction of the octahedral hydration shell of the aquated In3+ ion up to 300°C as well as the predominance of the tetrahedrally coordinated tetrachloroindium(III) species in chloride solutions at 350°C at the saturated vapour pressure. Indium chloride and hydroxy chloride complexes will play an important role in indium transport by hydrothermal fluids in the earth's crust.